Basics of Infertility - MohammedzadehAsl, Milad; Rani, Anjali; Agarwal, Nisha Rani (Basics of Infertility, Edition 1, 2024)
Infertility is a global health problem and is often neglected. The incidence of infertility is rising because of late marriages, job problems and lifestyle diseases. It is defined as the inability to become pregnant after one year of unprotected intercourse. It can be primary, secondary or unexplained. Infertility can be due to male factors, female factors or combined. In females, there can be PCOS, Endometriosis, Pelvic inflammatory disease, uterine anomalies, and ovarian failure. In males, it can be azoospermia and oligaestenia. The baseline investigations include semen analysis, hormone profile (LH, FSH, TSH, PROLACTIN, AMH) and follicular scan. Hysterosalpingography is done for the tubal patency test. Hysteroscopy and laparoscopy are done for tubal patency and uterine anomalies. The management of infertility ranges from simple counseling to advanced techniques like invitro fertilization and ICSI. The treatment should be individualized for every patient. Treatment of infertility is costly and financial aspects should be informed to patients in a very transparent manner. The medical aspect of infertility treatment is very important because it involves the human embryo. Informed written consent and preferably video consent should be taken. The consent form should be signed by both partners and also witness. The infertile couple waste lots of money and time in treatment. So proper time referral to an infertility centre is very important.